The Liquidity and Liquidity Distribution Effects in Emerging Markets The Case of Jordan - Vandenbussche, Jérôme (International Monetary Fund, 2009)
This paper analyzes the determinants of daily changes in Jordan''s interbank market overnight rate. It not only quantifies the classic liquidity effect, but also uncovers a liquidity distribution effect on both sides of the market, and shows that their magnitude is a decreasing and convex function of the level of excess reserves. It finds that the volatility of rate changes depends much more on the reserve surplus accumulated within a maintenance period than on the level of excess reserves. As Carpenter and Demiralp (2006), it uses the series of the central bank''s daily forecast errors to identify the liquidity effect